Development of multiferroics nanocomposites for Energy and Smart applications - Babu - Bitra; Rajesh (2023)
8 Development of flexible multiferroic 2D-nanocomposite prototype for their electric, magnetic, optical, multiferroic, and opto-magneto-electric" behaviour and respective "energy, smart (sensing and actuating), wide frequency applications by dispersing optimized NC2 nanopowders in PVDF polymer TOTAL 9 Development of stretchable multiferroic 2D-nanocomposite prototype for their electric, magnetic, optical, multiferroic, and opto-magneto-electric" behaviour and respective "energy, smart (sensing and actuating), wide frequency applications by dispersing NC2 optimized nanopowders in PDMS elastomer. TOTAL Otro(s) aspecto(s) que Ud. considere importante(s) en la evaluación del cumplimiento de objetivos planteados en la propuesta original o en las modificaciones autorizadas por los Consejos. RESULTS OBTAINED: For each specific goal, describe or summarize the results obtained. Relate each one to work already published and/or manuscripts submitted. In the Annex section include additional information deemed pertinent and relevant to the evaluation process. The maximum length for this section is 5 pages. (Arial or Verdana, font size 10). 1. Synthesis and characterization of Ni and Ti doped KBiFe2O5 1.1. Synthesis of KBiFe2O5 (KBF) through chemical precipitation route (Task 1:M1) KBF was prepared from chemical co-precipitation method by mixing highly pure KNO3, Bi(NO3)3 · 5H2O, and Fe(NO3)3 · 9H2O, Ni(NO3)2.6H2O, Ti(NO3)4.4H2O (required stoichiometric ratio) to 200 ml of double distilled water and stirred for about 30 min to form a clear solution. A 2M of precipitating agent (Ammonia) was prepared mixed in drop wise to the metal nitrate solution until the pH of the solution to reach 9.3 (same was maintained for the all the samples) to get the reaction product in the form of precipitation. This precipitate will be kept at room temperature and washed several times with double distilled water to remove un-reactant products and then filtered. The Final precipitate powders were dried in hot air oven at 60oC/1hr and annealed at ...